DAMPAK EFEKTIVITAS PENERAPAN SISTEM REWARD DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DIREKTORAT JENDERAL PAJAK (DJP) - Muhammad Kurniawan Al Bashir Tamar; Fajar Gustiawaty Dewi; Rindu Rika Gamayuni (ITB AAS INDONESIA, 2022)
Employees are the main assets of an agency and have an important role in an agency, namely as thinkers, planners, and controllers of agency activities. Good employee performance is very important in supporting the smooth work that is the burden and responsibility of an agency. The purpose of this study is to examine more deeply the impact of whether the performance of employees who are given financial rewards is more effective than the performance of employees who are given non-financial rewards and whether the performance of employees who are given a charismatic leadership style is more effective than the performance of employees who are given an authoritarian leadership style. further analyze the performance of employees who are given financial rewards and charismatic leadership styles are more effective than those who are given non-financial rewards and authoritarian leadership styles at the Directorate General of Taxes (DGT) in Lampung Province. The mean difference test and Analysis of Variance (ANOVA) test were used for the comparison results. The results of the tests carried out showed that there was a significant (significant) difference between the performance of employees who were given financial and non-financial rewards at the Directorate General of Taxes (DGT) in Lampung Province. There is a significant (significant) difference between the performance of employees who are given a charismatic leadership style and an authoritarian leadership style. The performance of employees who are given financial rewards and a charismatic leadership style simultaneously is different from the performance of employees who are given non-financial rewards and an authoritarian leadership style simultaneously at the Directorate General of Taxes (DGT) in Lampung Province.